2011
DOI: 10.1007/978-3-642-23644-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Environment-Sensitive Malware

Abstract: I hereby declare that I am the sole author of this thesis, that I have exhaustively specified all sources and resources used, and that parts of this thesis-including tables, maps and figures-if taken from other works or from the Internet, whether copied literally or by sense, all have been marked as replications including a citation of the source. Hiermit erkläre ich, dass ich diese Arbeit selbständig verfasst habe, dass ich die verwendeten Quellen und Hilfsmittel vollständig angegeben habe und dass ich die St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(90 citation statements)
references
References 28 publications
0
90
0
Order By: Relevance
“…In 2009, according to [2] 0.3 to 12.5 percent of the samples submitted to Anubis were able to detect the sandbox and refuse to run. In [22] it is shown that evasive malware was being actively developed and distributed in 2011. While overcoming this limitation is beyond the scope of our work, we can note that the problem of evasive malware is well mitigated by collecting data outside the malware execution scope.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…In 2009, according to [2] 0.3 to 12.5 percent of the samples submitted to Anubis were able to detect the sandbox and refuse to run. In [22] it is shown that evasive malware was being actively developed and distributed in 2011. While overcoming this limitation is beyond the scope of our work, we can note that the problem of evasive malware is well mitigated by collecting data outside the malware execution scope.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Instead of analyzing the program instructions, the behavior of the program under analysis is monitored and evaluated. Several applications have been developed based on dynamic analysis sandboxes to monitor botnet traffic [11], obtain unpacked and unencrypted malware samples [12], [13], automatically obtain malware mitigation procedures [14] and detect unknown evasion techniques [15]. Several such tools exist today for both, research and commercial purposes.…”
Section: B Malware Analysismentioning
confidence: 99%
“…Dione only requires basic disk access information that can be obtained by many types of sensors, including both physical hardware sensors and virtualizationbased sensors. It can, therefore, be used to analyze and detect malware that utilizes anti-sandbox or virtualization-evasion techniques, which have become increasingly common [3,8,19].…”
Section: Introductionmentioning
confidence: 99%